Gender, ethnicity, ethnic identity, and language choices of Malaysian youths: the case of the family domain - Granhemat, Mehdi; Abdullah, Ain Nadzimah (Australian International Academic Centre, 2017)
This study examined the relationships between gender, ethnicity, ethnic identity, and language choices of Malaysian multilingual youths in the family domain of language use. Five hundred undergraduate students who belonged to different Malaysian ethnic groups were selected as participants of the study. The participant aged between 17 to 25 years old. To select the participants, a random proportional stratified sampling strategy was developed. A self administered questionnaire survey comprising three sections was used for gathering information about participants’ demographic profiles, their language choices in the family domain, and the concepts of their ethnic identity. To make analyses about the most used languages of the participants and the relationships between variables, SPSS software was run. Descriptive statistics was used to describe the participants’ profiles as well as participants’ used languages in the family domain of language use. Inferential statistics was used to examine relationships between variables. According to results of the study, in the family domain five codes were mostly used by the participants. These five codes were respectively, the Malay language, mixed use of Malay and English, Chinese, Mixed use of Chinese and English, and English. Furthermore, in the family domain, gender did not exert any influence on the choice of language of the multilingual participants, but ethnicity was found to be a determinant of language choice. Ethnic identity was found to influence the language choices of the Malays as well, but it did not affect the Chinese and Indian participants’ language choices in this domain of language use.